Membrane protein recycling from the vacuole/lysosome membrane - Suzuki, Sho W. (J Cell Biol, 2018)
The lysosome (or vacuole in yeast) is the central organelle responsible for cellular degradation and nutrient storage. Lysosomes receive cargo from the secretory, endocytic, and autophagy pathways. Many of these proteins and lipids are delivered to the lysosome membrane, and some are degraded in the lysosome lumen, whereas others appear to be recycled through unknown pathways. In this study, we identify the transmembrane autophagy protein Atg27 as a physiological cargo recycled from the vacuole. We reveal that Atg27 is delivered to the vacuole membrane and then recycled using a two-step recycling process. First, Atg27 is recycled from the vacuole to the endosome via the Snx4 complex and then from the endosome to the Golgi via the retromer complex. During the process of vacuole-to-endosome retrograde trafficking, Snx4 complexes assemble on the vacuolar surface and recognize specific residues in the cytoplasmic tail of Atg27. This novel pathway maintains the normal composition and function of the vacuole membrane.